Hacking the Electorate : How Campaigns Perceive Voters - Hersh, Eitan D. (Cambridge : Cambridge University Press, 2015)
Hacking the Electorate is the most comprehensive study to date about the consequences of campaigns using microtargeting databases to mobilize voters in elections. Eitan Hersh follows the trail from data to strategy to outcomes. Hersh argues that most of what campaigns know about voters comes from a core set of public records. States vary in the kinds of records they collect from voters - and these variations in data across the country mean that campaigns perceive voters differently in different areas. Consequently, the strategies of campaigns and the coalitions of voters who are mobilized fluctuate across the country because of the different ways campaigns perceive the electorate. Data policies influence campaigns, voters and, increasingly, public officials.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).